2009
DOI: 10.4161/cc.8.3.7643
|View full text |Cite
|
Sign up to set email alerts
|

Molecular pharmacology of phosphatidylinositol 3-kinase inhibition in human glioma

Abstract: Gliomas are primary brain tumors with poor prognosis that exhibit frequent abnormalities in phosphatidylinositol 3-kinase (PI3 kinase) signaling. We investigated the molecular mechanism of action of the isoform-selective class I PI3 kinase and mTOR inhibitor PI-103 in human glioma cells. The potent inhibitory effects of PI-103 on the PI3 kinase pathway were quantified. PI-103 and the mTOR inhibitor rapamycin both inhibited ribosomal protein S6 phosphorylation but there were clear differences in the response of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
54
1

Year Published

2009
2009
2013
2013

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(62 citation statements)
references
References 44 publications
7
54
1
Order By: Relevance
“…There are so far only few studies using PI3K inhibitors as chemosensitizers, for example in T-cell acute lymphoblastic leukemia (Chiarini et al, 2009), glioblastoma (Guillard et al, 2009;Westhoff et al, 2009) or chronic lymphocytic leukemia (Niedermeier et al, 2009), and little is yet known about the underlying molecular mechanisms of sensitization. Thus, the novelty of our study resides in particular in the elucidation of the molecular events mediating the cooperative cytotoxicity of the recently developed PI3K inhibitor PI103 and anticancer drugs, such as Doxorubicin, by demonstrating that chemosensitization by PI103 critically depends on mitochondrial outer membrane permeabilization as the result of a shift towards pro-apoptotic Bcl-2 proteins.…”
Section: Targeting Pi3k In Neuroblastomamentioning
confidence: 99%
“…There are so far only few studies using PI3K inhibitors as chemosensitizers, for example in T-cell acute lymphoblastic leukemia (Chiarini et al, 2009), glioblastoma (Guillard et al, 2009;Westhoff et al, 2009) or chronic lymphocytic leukemia (Niedermeier et al, 2009), and little is yet known about the underlying molecular mechanisms of sensitization. Thus, the novelty of our study resides in particular in the elucidation of the molecular events mediating the cooperative cytotoxicity of the recently developed PI3K inhibitor PI103 and anticancer drugs, such as Doxorubicin, by demonstrating that chemosensitization by PI103 critically depends on mitochondrial outer membrane permeabilization as the result of a shift towards pro-apoptotic Bcl-2 proteins.…”
Section: Targeting Pi3k In Neuroblastomamentioning
confidence: 99%
“…1,2 The prognosis of patients with GBM is very poor, mainly because it remains therapeutic challenge, and the conventional postsurgical chemotherapeutic agents exhibit limited effects. 3,4 Temozolomide (TMZ), as currently the most promising chemotherapeutic drug, is applied to treat malignant glioma, including GBM.…”
Section: Introductionmentioning
confidence: 99%
“…PI-103 is a potent and selective inhibitor of class I phosphatidylinositide 3-kinases, and also of mTOR and DNA-PK, which blocked the proliferation of human cancer cells in vitro and caused pharmacodynamic biomarker effects consistent with target inhibition (29)(30)(31). PI-103 showed therapeutic activity against a range of human tumor xenografts, exhibiting inhibition of angiogenesis, invasion, and metastasis, as well as direct antiproliferative effects (29,31,32).…”
Section: Introductionmentioning
confidence: 99%
“…With our collaborators Hayakawa et al (25)(26)(27)(28), we have previously reported the discovery of three new series of phosphatidylinositide 3-kinase inhibitors and described the detailed pharmacologic properties of a novel synthetic lead compound of the tricyclic pyridofuropyrimidine class, PI-103 (29,30). PI-103 is a potent and selective inhibitor of class I phosphatidylinositide 3-kinases, and also of mTOR and DNA-PK, which blocked the proliferation of human cancer cells in vitro and caused pharmacodynamic biomarker effects consistent with target inhibition (29)(30)(31).…”
Section: Introductionmentioning
confidence: 99%